UZBEKISTAN AND AFGHANISTAN IN THE CONTEXT OF ENSURING REGIONAL SECURITY. (Multidisciplinary Journal of Science and Technology, 2025)
The security dynamics between Uzbekistan and Afghanistan play a crucial role in maintaining stability in Central Asia. This essay explores Uzbekistan’s evolving foreign policy toward Afghanistan, particularly in the aftermath of the Taliban’s return to power. The analysis highlights Uzbekistan’s diplomatic initiatives, economic engagements, and security strategies aimed at fostering regional stability. Special attention is given to key infrastructure projects, such as the Mazar-i-Sharif–Kabul–Peshawar railway, which strengthens economic ties while promoting peace. Additionally, the essay examines the security challenges posed by terrorism, drug trafficking, and border instability, emphasizing the need for multilateral cooperation among Central Asian states. By integrating economic and diplomatic efforts, Uzbekistan seeks to position itself as a mediator in Afghanistan’s stabilization process, underscoring the broader implications for regional and global security.